Seismic site studies in Pendik - Tuzla regions in Istanbul - Er, Leyla Aslı. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2010., 2010)
The objective of this study is to identify soil amplification and soil fundamental frequency in the area between Pendik and Tuzla, the southeast of Istanbul city, and showing how the values of soil amplification, dominant period and frequency will change according to layer thickness overlying the bedrock. Pendik - Tuzla regions were selected according to variation of bedrock depth which changes from 65 to 150 meters and topographical changes from north to south representing a valley type structure. According to geological formations, and topographic structure, 64 measurement points were selected for a horizontal/vertical spectral ratios method, (Nakamura's method) in Pendik–Tuzla area. In the same area, OYO Company collected data using Suspension Ps logging and Refraction Microtremor methods. I used these data to calculate amplification and dominant period using Shake 91 program for different 56 measurement points. Also, dominant periods were calculated using empirical formulas. The results obtained from site measurements and model studies were correlated with each other and were displayed in contour maps and interpreted according to geology, topography and the geological distributions of bedrock depths and the formation types in the investigated area. According to the H/V and model studies, amplifications on the three regions, Aydınlı, Orhanlı and south of the study areas were found much more bigger than surrounding stable areas. These three regions consist of approximately reaching up 120 m thickness of Cenozoic aged, Sultanbeyli and Kuşdili Formations, overlying the Paleozoic bedrocks. Besides, the highest fundamental soil period values calculating from both studies are estimated in these regions. As a result through investigation and significant observation of both of these studies, thickness of sedimentary layers overlying bedrock and soil dynamic properties of these structure layers have a great effect on the evaluation of seismic site studies, soil transfer function and dominant period and frequencies.
Keywords: Soil dynamics.; Earthquakes -- Istanbul (Turkey)